187. Significant Decline in Carbapenem Use with Multifaceted Antimicrobial Stewardship Program (ASP) Interventions. (31st December 2020) - Kaushik, Ashlesha; Gupta, Sandeep; Lettow, Erin; Lundsgaard, Jenna; Thieman, Corey; Fullas, Fekadu; Padomek, Michael
Abstract: Background: Per World Health Organization, carbapenems should be key targets for antibiotic stewardship programs. Methods: A multifaceted antimicrobial stewardship program (ASP) was implemented in January 2018 at a 160-bed tertiary care center serving the tristate area of Iowa, South Dakota and Nebraska. Carbapenem use during pre ASP intervention period (P1: 07/01/2016-12/31/2017) was compared with ASP intervention period (P2: 01/01/2018-06/30/2019). ASP interventions included: providing educational pearls in monthly physician newsletter; educational posters in high-traffic provider areas; suppression of carbapenem results on microbiology susceptibility reports; distributing monthly carbapenem use data to providers; provider counseling for appropriate ordering; creating carbapenem alternative alert in order-entry software; generating pharmacy decision-support software algorithms to aid in identifying intervention opportunities; removing carbapenems from order-sets where appropriate. Additional ASP pharmacist interventions: limiting double antibiotic coverage for pseudomonas/anaerobes; de-escalation recommendations. Results: Carbapenem use declined significantly from a mean of 64.81 days of therapy (DOT) per 1000 patient days during P1 to 8.91 DOT per 1000 patient days in P2 (p< 0.001). All hospital units showed a significant decrease in carbapenem use, with intensive care step-down unit noting 85.7% reduction (p < 0.00001); floors (medicine, pediatric, surgery) with 61.6% reduction (p< 0.00001); and intensive care units with 52% reduction (p< 0.00001) during P2 compared to P1. Defined daily doses per 1000 patient days decreased from 314.9 in P1 to 93.4 in P2 (p< 0.00001). During P2, 58.3% (132/228) of carbapenem orders were found to be appropriate compared to 37.5% (190/506) in P1 (p< 0.00001). Sensitivity profile for Pseudomonas aeruginosa improved from 86% carbapenem sensitivity during P1 to 89% in P2. No Carbapenem Resistant Enterobacteriaceae isolates were identified. Cost savings of 643 per 1000 patient days were recognized in P2 as a result of reduced carbapenem use. Conclusion: There was a significant decline in total carbapenem utilization, an increase in proportion of appropriate use and considerable cost savings as a result of ASP interventions. Disclosures: All Authors : No reported disclosures